Graphene oxide loaded nano polyhedral cerium oxide antifouling agent as well as preparation method and application thereof

By using graphene oxide-loaded nanopolyhedral cerium oxide compounds in the antifouling coating, the problem of high preparation cost or poor antifouling performance in the prior art is solved, and low-cost and efficient antifouling performance is achieved.

CN119505591APending Publication Date: 2025-02-25CHINA HUBEI LONGZHONG LABORATORY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411532003.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, there is a problem that the preparation cost of antifouling coatings is high or the antifouling performance is poor.

Method used

By mixing the cerium salt solution and the graphene oxide suspension, adding alkali solution, and carrying out hydrothermal reaction, graphene oxide supports nanopolyhedral cerium oxide compound, fixing the nano cerium oxide on the surface of graphene oxide to improve its antibacterial properties.

Benefits of technology

The low-cost preparation of graphene oxide-loaded nanopolyhedral cerium oxide antifouling agent is achieved, which improves its antibacterial and antifouling properties and reduces the potential harm to marine organisms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505591A_ABST
    Figure CN119505591A_ABST
Patent Text Reader

Abstract

The invention relates to a graphene oxide loaded nano polyhedral cerium oxide antifouling agent and a preparation method and application thereof, the preparation method comprises the following steps: (1) mixing a cerium salt solution and a graphene oxide suspension, adding an alkali liquor, uniformly mixing to obtain a first mixed solution, and carrying out a hydrothermal reaction on the mixed solution to obtain a second mixed solution; and (2) centrifugally washing the second mixed solution, freeze-drying and purifying to obtain the graphene oxide loaded nano polyhedral cerium oxide compound. According to the preparation method disclosed by the invention, cerium oxide nanoparticles grow on the surface of graphene oxide in a coordination bonding manner, so that nano polyhedral cerium oxide powder is fixed on the surface of graphene oxide, and the antibacterial property of cerium oxide is improved; the preparation method is simple in process and low in cost; the obtained graphene oxide loaded nano polyhedral cerium oxide antifouling agent is a composite material, and is high in oxidation resistance and adsorption capacity and good in antifouling property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano-synthesis, and in particular relates to a graphene oxide-loaded nano-polyhedral cerium oxide antifouling agent and a preparation method and application thereof. Background Art

[0002] Marine biofouling refers to the damage to underwater facilities caused by the attachment and invasion of marine organisms, which seriously restricts the development of ships and marine engineering. Constructing green antifouling coatings is an important means of marine antifouling.

[0003] At present, green antifouling coatings include bionic materials, which mainly imitate the surface structure of certain organisms in nature (such as shark skin, dolphin skin, etc.), design materials with low friction properties, and reduce the chance of attachment of marine organisms. Such materials usually have super hydrophobic or super hydrophilic properties, which can effectively reduce the risk of biological fouling. However, bionic materials often require complex manufacturing processes, which leads to relatively high production costs, and in order to improve antifouling performance, they usually use chemically modified surfaces, which may release harmful substances and have adverse effects on marine organisms.

[0004] In order to reduce toxicity and improve biocompatibility, bioactive ingredients such as haloperoxidase can also be used. Haloperoxidase is a type of natural antifouling agent secreted by marine algae, which can prevent or reduce the attachment of marine fouling organisms to the surface of ships and other surfaces by producing halogen compounds, thus achieving green antifouling. However, natural haloperoxidase is difficult to extract and unstable, resulting in poor antifouling performance, which limits its application. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, provide a graphene oxide loaded nano-polyhedral cerium oxide antifouling agent and a preparation method and application thereof, and solve the technical problems of high preparation cost or poor antifouling performance of the antifouling coating in the prior art.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a graphene oxide-supported nano-polyhedral cerium oxide antifouling agent, comprising the following steps: (1) mixing a cerium salt solution and a graphene oxide suspension, adding an alkali solution and mixing evenly to obtain a first mixed solution, and subjecting the mixed solution to a hydrothermal reaction to obtain a second mixed solution; (2) The second mixed solution is centrifuged, washed, freeze-dried and purified to obtain a graphene oxide-supported nano-polyhedral cerium oxide compound.

[0007] In a second aspect, the present invention provides a graphene oxide-loaded nano-polyhedral cerium oxide antifouling agent prepared by the above preparation method.

[0008] In a third aspect, the present invention provides a use of the above-mentioned graphene oxide-loaded nano-polyhedral cerium oxide antifouling agent in the preparation of a marine antifouling coating.

[0009] Compared with the prior art, the beneficial effects of the present invention include: The invention controls the process sequence of mixing a cerium salt solution and a graphene oxide suspension first and then adding an alkali solution to adjust the pH value, so that the graphene oxide reacts chemically with the surface of the cerium oxide powder, and grows cerium oxide nanoparticles on the surface of the graphene oxide by coordination bonding, thereby fixing the nano-polyhedron cerium oxide powder on the surface of the graphene oxide and improving the antibacterial performance of the cerium oxide. The preparation method of the invention has simple procedures and low costs. The obtained graphene oxide-loaded nano-polyhedron cerium oxide antifouling agent is a composite material with strong oxidation resistance and adsorption capacity and good antifouling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 TEM images of nano-polyhedral cerium oxide (CeO2) and graphene oxide-supported nano-polyhedral cerium oxide (GO-CeO2) of the present invention, wherein (a) is CeO2 prepared according to the steps of Example 1 without adding graphene oxide, (b) is GO-CeO2-1 of Example 1, (c) is GO-CeO2-2 of Example 2, and (d) is GO-CeO2-3 of Example 3, (-1) are all TEM images, and (-2) is the HRTEM image corresponding to (-1); Figure 2 is a TEM image of cerium oxide in Comparative Example 1 (scale 100 nm); Figure 3 It is a graph showing the anti-biofilm effect of graphene oxide loaded with nano-polyhedral cerium oxide of the present invention; Figure 4 It is a curve diagram of the antibacterial rate of the graphene oxide loaded nano-polyhedral cerium oxide of the present invention. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0012] In the field of marine antifouling, the production cost of bionic materials in current green antifouling coatings is relatively high or may release harmful substances, and natural antifouling agents such as haloperoxidase are difficult to extract and unstable, resulting in poor antifouling performance; in view of the above-mentioned defects, finding an antifouling agent with good antibacterial performance and easy to obtain is the focus of current research. The present invention provides a graphene oxide-loaded nano-polyhedral cerium oxide antifouling agent, a preparation method and an application thereof. The prepared graphene oxide-loaded nano-polyhedral cerium oxide has good antibacterial performance and can be used as an antifouling agent in the field of marine antifouling.

[0013] In a first aspect, the present invention provides a method for preparing a graphene oxide-supported nano-polyhedral cerium oxide antifouling agent, comprising the following steps: (1) mixing a cerium salt solution and a graphene oxide suspension, adding an alkali solution and mixing evenly to obtain a first mixed solution, and subjecting the mixed solution to a hydrothermal reaction to obtain a second mixed solution; (2) The second mixed solution is centrifuged, washed, freeze-dried and purified to obtain a graphene oxide-supported nano-polyhedral cerium oxide compound.

[0014] In the present invention, the order of adding raw materials needs to be controlled. The cerium salt solution and the graphene oxide suspension are first mixed, and then the alkali solution is added to mix. If the cerium salt solution and the alkali solution are mixed first and then the graphene oxide is added, cerium oxide is directly generated, and there is no chemical crosslinking with the graphene oxide, and the effect of promoting the improvement of the antifouling performance cannot be achieved.

[0015] Preferably, in step (1), the cerium salt includes cerium nitrate; the ratio between the cerium salt and graphene oxide is 2mmol: (7.2-28.8)mg, including but not limited to 2mmol: 7.2mg, 2mmol: 10mg, 2mmol: 14.4mg, 2mmol: 18mg, 2mmol: 20mg, 2mmol: 25mg, 2mmol: 28.8mg, etc.

[0016] Preferably, in the first mixed solution of step (1), the concentration of the cerium salt is 0.04-0.06 mol / L; the concentration of the alkali is 0.08-0.12 mol / L. Specifically, the concentration of the cerium salt includes but is not limited to 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, etc.; the concentration of the alkali includes but is not limited to 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.11 mol / L, 0.12 mol / L, etc.

[0017] Preferably, in step (1), the alkali in the alkali solution comprises sodium hydroxide.

[0018] Preferably, in step (1), the hydrothermal reaction is carried out at 75-85° C. for 22-26 hours.

[0019] Preferably, in step (1), after the cerium salt solution and the graphene oxide suspension are evenly mixed, an alkali solution is added and stirred for 25 to 35 minutes to obtain a first mixed solution.

[0020] Preferably, in step (2), the centrifugation conditions are: centrifugation at a speed of 8000 to 12000 rpm for 5 to 15 minutes, and then resuspending in deionized water until the supernatant is neutral.

[0021] Preferably, in step (2), the freeze-drying conditions are: freezing at -60 to -80°C for 10 to 14 hours and then placing in a vacuum chamber for drying.

[0022] In a second aspect, the present invention provides a graphene oxide-loaded nano-polyhedral cerium oxide antifouling agent prepared by the above preparation method.

[0023] Preferably, the particle size of the nano-polyhedral cerium oxide is 5 to 10 nm.

[0024] In a third aspect, the present invention provides a use of the above-mentioned graphene oxide-loaded nano-polyhedral cerium oxide antifouling agent in the preparation of a marine antifouling coating.

[0025] The main mechanism of action and advantages of the present invention are: The present invention uses a chemical reaction to connect graphene oxide and the surface of cerium oxide powder in the form of chemical bonds, and fixes the nano-polyhedron cerium oxide powder on the surface of graphene oxide. There are some active sites on the surface of cerium oxide powder, such as oxygen vacancies and hydroxide complexes on the surface of cerium oxide; the oxygen-containing functional groups (such as hydroxyl and carboxyl) on the surface of graphene oxide can react with Ce 3+ and Ce 4+ Ionic interactions allow cerium oxide nanoparticles to grow on the surface of graphene oxide by means of coordination bonding. The antibacterial properties of cerium oxide are improved by fixing cerium oxide on the surface of graphene oxide. Compared with nano-cerium oxide powder, this composite material has enhanced antioxidant and adsorption capabilities. This improves the antifouling properties of graphene oxide-loaded nano-polyhedral nano-cerium oxide powder.

[0026] The present invention is further described in detail below through specific examples. The graphene oxide used was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a concentration of 2 mg / mL. Cerium nitrate hexahydrate was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a purity of 99.5%. Sodium hydroxide was purchased from Sinopharm Chemical Reagent Co., Ltd. with a purity of 96%.

[0027] Example 1 A method for preparing a graphene oxide-loaded nano-polyhedral cerium oxide antifouling agent comprises the following steps: 3.6 mL of 2 mg / mL graphene oxide suspension was added to 16.4 mL of deionized water to obtain solution A, 0.868 g (2 mmol) of cerium nitrate hexahydrate was added to 10 mL of deionized water to obtain solution B, and 0.16 g (4 mmol) of sodium hydroxide was added to 10 mL of deionized water to obtain solution C.

[0028] First, mix solution A and solution B evenly, then add solution C and stir for 30 minutes. Pour into a reactor and react at 80°C for 24 hours. After natural cooling, centrifuge at 10,000 rpm for 10 minutes, resuspend in deionized water until the supernatant is neutral, freeze at -70°C for 12 hours, and dry in a vacuum chamber at a vacuum degree of 2 Pa to obtain graphene oxide-supported nano-polyhedral cerium oxide, recorded as GO-CeO2-1.

[0029] Example 2 The only difference from Example 1 is that 7.2 mL of 2 mg / mL graphene oxide suspension is added to 12.8 mL of deionized water to obtain solution A, and the other steps and conditions are the same as those in Example 1; graphene oxide-loaded nano-polyhedral cerium oxide is obtained, which is recorded as GO-CeO2-2.

[0030] Example 3 The only difference from Example 1 is that 14.4 mL of a graphene oxide suspension with a concentration of 2 mg / mL is added to 5.6 mL of deionized water to obtain solution A, and the other steps and conditions are the same as those in Example 1; graphene oxide-loaded nano-polyhedral cerium oxide is obtained, which is recorded as GO-CeO2-3.

[0031] Comparative Example 1 A method for preparing cerium oxide comprises the following steps: Add 0.868 g of cerium nitrate hexahydrate to 30 mL of deionized water to obtain solution A, and add 1.6 g of sodium hydroxide to 10 mL of deionized water to obtain solution B. Mix solutions A and B evenly and stir for 30 minutes. Pour into a reactor and react at 80°C for 24 hours. After natural cooling, centrifuge until the supernatant is neutral and freeze-dry to obtain rod-shaped cerium oxide CeO2.

[0032] Performance Testing The products obtained from the above examples and comparative examples were subjected to transmission electron microscopy (TEM), anti-biofilm and antibacterial tests, and the main test conditions and results are as follows.

[0033] (1) TEM test: Prepare a suspension of graphene oxide loaded with cerium oxide and dilute it to a transparent state, shake the suspension until it is uniform, and use a pipette to drop a small amount of the suspension onto a copper sheet and air-dry (the cerium oxide test conditions of the comparative example are the same as those of the example). The results are as follows: Figure 1 and Figure 2 shown.

[0034] Depend on Figure 1 It can be seen from (b-1) and (b-2) that the graphene oxide-loaded cerium oxide nanocomposite particles obtained in Example 1 are surrounded by (111) planes with a plane spacing of 3.12 Å and (200) planes with a plane spacing of 2.70 Å; the uniform distribution of nanocerium oxide particles on the graphene oxide sheets further confirms the successful preparation of GO-CeO2-1.

[0035] Depend on Figure 1 As can be seen from (c-1) and (c-2), the graphene oxide-loaded cerium oxide nanocomposite particles obtained in Example 2 are surrounded by (111) planes with a plane spacing of 3.12 Å; the uniform distribution of nano-cerium oxide particles on the graphene oxide sheets confirms the successful synthesis of GO-CeO2-2. Compared with GO-CeO2-1 in Example 1, GO-CeO2-2 in Example 2 shows a decrease in nano-cerium oxide particles on the graphene oxide sheets.

[0036] Depend on Figure 1 As can be seen from (d-1) and (d-2), the graphene oxide-supported cerium oxide nanocomposite particles obtained in Example 3 are surrounded by (111) planes with a plane spacing of 3.12 Å. The uniform distribution of nano-cerium oxide particles on the graphene oxide sheet confirms the successful synthesis of GO-CeO2-3. Compared with GO-CeO2-2 of Example 2, GO-CeO2-3 of Example 3 shows a significant reduction in the number of nano-cerium oxide particles on the graphene oxide sheet.

[0037] On the basis of Example 1, graphene oxide was not added, and the remaining steps and conditions were the same as those in Example 1. The obtained product CeO2 was as follows: Figure 1 As shown in (a-1), the CeO2 is a nano-polyhedron; Figure 1 (a-1) and Figure 2 By comparison, it can be seen that the amount of alkali used in Comparative Example 1 is adjusted relative to that in Example 1, and the cerium oxide obtained is in the shape of rods.

[0038] (2) Anti-biofilm test: 12 experimental groups were prepared according to the following operation. The concentration of E. coli in LB broth medium was 10 7 / mL, divided into the following groups: A1: Escherichia coli; A2: E. coli + 25 mmol / L NH4Br + 1 mmol / L H2O2; B1 / C1 / D1 / E1 / F1: E. coli + 100 mg / L five different nanoparticles (GO, CeO2, GO-CeO2-1, GO-CeO2-2, GO-CeO2-3); B2 / C2 / D2 / E2 / F2: Escherichia coli + 25 mmol / L NH4Br + 1 mmol / L H2O2+ 100 mg / L five different nanoparticles.

[0039] The above different groups were incubated in a 96-well plate at 37 °C for 24 hours. After 24 hours of culture, the suspension in the 96-well plate was discarded. The formed biofilm was washed three times with sterile 0.9 wt.% NaCl solution and then fixed with 2.5% glutaraldehyde for 20 minutes. The formed biofilm was stained with 200 μL 0.1 wt.% crystal violet for 30 minutes. Then, the plate was washed three times with 0.9 wt.% NaCl solution to remove the floating crystal violet. After air drying, 200 μL 95% ethanol solution was used to dissolve the cell-bound crystal violet. The staining solution was pipetted into a 96-well plate to record the optical density value (OD) at 590 nm using a microplate reader. 590 ). The results are as follows Figure 3 shown.

[0040] from Figure 3 It can be seen that the graphene oxide-loaded polyhedral cerium oxide (D1, D2) of Example 1, the graphene oxide-loaded polyhedral cerium oxide (E1, E2) of Example 2, and the graphene oxide-loaded polyhedral cerium oxide (F1, F2) of Example 3 all have a more obvious effect in inhibiting the formation of biofilm than the cerium oxide (C1, C2) of Comparative Example 1.

[0041] Specifically, comparison of the A1 and A2 control groups showed that H2O2 and NH4Br had the least effect on E. coli biofilm formation. OD 590 nmThe value is less than that of Group A1, which is attributed to the antibacterial effect of the nanocomposite. When the biofilm biomass of the control group A1 is considered as 100%, the order of the biomass of the nanocomposite added is: GO-CeO2-2 (33%) < GO-CeO2-1 (43%) < GO-CeO2-3 (48%) < CeO2 (68%) < GO (80%). The GO-CeO2-2 nanocomposite exhibits the highest intrinsic antibacterial performance because graphene oxide provides the necessary H2O2 for the enzymatic activity of cerium oxide. Monolayer graphene oxide and smaller cerium oxide nanoparticles can easily penetrate the cell membrane, resulting in bacterial death. Compared with Group B1 (regarded as 100%), the biofilm biomass of Groups B2, C2, D2, E2, and F2 is significantly reduced, and the order is as follows: GO-CeO2-2 (16%) < GO-CeO2-1 (21%) < GO-CeO2-3 (24%) < CeO2 (42%) < GO (70%), which corresponds to the enzymatic activity of these nanocomposites. The enhanced biofilm inhibition under bromination oxidation conditions indicates that the enzymatic activity of GO-CeO2 plays an important role, and the enzymatic activity is more effective in preventing biofilm formation. This shows that the significant anti-biofilm activity is mainly attributed to the enzymatic activity of the GO-CeO2 nanocomposite.

[0042] Therefore, the graphene oxide-supported polyhedral cerium oxide obtained in each embodiment of the present invention can still directly exhibit effective anti-biofilm activity without adding NH4Br and H2O2, indicating that the graphene oxide-supported polyhedral cerium oxide of the present invention has excellent antifouling performance and can effectively save the antifouling cost.

[0043] (3)Antibacterial test: The concentration of Escherichia coli in 0.9 wt.% NaCl solution is 10 6 cells / mL, and 6 groups are set as follows: Control group 1: control1, Escherichia coli suspension; Control group 2: control2, Escherichia coli suspension + 25 mmol / L NH4Br + 0.1 mmol / L H2O2; 5 experimental groups: Escherichia coli suspension + 25 mmol / L NH4Br + 0.1 mmol / L H2O2 + 100 mg / L 5 different nanoparticles ((1) GO, (2) CeO2, (3) GO-CeO2-1, (4) GO-CeO2-2, (5) GO-CeO2-3).

[0044] Each group was incubated at 37°C in a pre-sterilized 24-well plate. After 4 h of incubation, the bacterial suspension was serially diluted with sterile 0.9 wt.% NaCl solution, and 100 μL of the dilution was evenly distributed on the nutrient agar plate. After 24 h of incubation at 37°C, a photo of each agar plate was taken for antibacterial analysis. The bacterial colony forming units on the agar plate were counted using ImageJ software to quantitatively analyze the antibacterial efficiency. The test results are shown in Figure 2. Figure 4 shown.

[0045] Depend on Figure 4 It can be seen that the graphene oxides of Examples 1-3 support polyhedral cerium oxide ( Figure 4 The antibacterial properties of (3) to (5)) are better than those of cerium oxide ( Figure 4 (2)) is high and significantly higher than that of single graphene oxide ( Figure 4 In (1)), the antibacterial rate can reach 91.4-97.6% (i.e., the bacterial survival rate is below 9%), which shows that graphene oxide promotes the antibacterial properties of nano-cerium oxide.

[0046] Specifically, the antibacterial efficiency: GO-CeO2-2 (97.6%) > GO-CeO2-1 (91.9%) > GO-CeO2-3 (91.4%) > CeO2 (90.5%) > GO (74.2%), corresponding to their enzyme activities. It is noteworthy that GO-CeO2-2 showed the highest enzyme activity, resulting in excellent antibacterial efficiency. This high efficiency inhibits biofilm by reducing the concentration of fouling organisms. The excellent antibacterial performance of GO-CeO2-2 is attributed to the optimal concentration of graphene oxide and cerium oxide. The excellent antibacterial performance of GO-CeO2-2 is mainly due to its excellent enzyme activity and high Ce 3+ In GO-CeO2-1, low GO content resulted in reduced antibacterial efficiency due to relatively insufficient active sites, reduced (reactive oxygen) ROS production, weakened physical damage, particle aggregation, and limited synergistic effects. In GO-CeO2-3, low concentrations of CeO2 impaired antibacterial activity by reducing the production of ROS and HOBr, weakening synergistic interactions, and reducing the structural stability of GO.

[0047] Therefore, from the comparison of the antibacterial properties of Examples 1-3, it can be seen that with the increase in the amount of graphene oxide, the antibacterial property of the obtained graphene oxide-loaded polyhedral cerium oxide first increases and then decreases, which shows that the amount of graphene oxide also affects the antibacterial properties of the obtained product. The preferred ratio of cerium salt to graphene oxide in the present invention is 2 mmol: (7.2-28.8) mg. Considering the cost, it is further preferably 2 mmol: (7.2-14.4) mg, and more preferably 2 mmol: 14.4 mg.

[0048] Different from the prior art, the present invention provides a graphene oxide-supported nano-polyhedral cerium oxide antifouling agent and a preparation method and application thereof, wherein the graphene oxide-supported nano-polyhedral cerium oxide is prepared by a hydrothermal reaction. Under the hydrothermal conditions, the oxygen-containing functional groups (such as hydroxyl and carboxyl) on the surface of the graphene oxide can react with Ce 3+ and Ce 4+ Ionic interactions allow cerium oxide nanoparticles to grow on the surface of graphene oxide by means of coordination bonding. By fixing cerium oxide on the surface of graphene oxide, the antibacterial properties of cerium oxide are improved. This composite material combines the high conductivity and large specific surface area of ​​graphene oxide with the excellent catalytic properties and antibacterial properties of cerium oxide, and has broad application prospects.

[0049] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a graphene oxide-supported nano-polyhedral cerium oxide antifouling agent, characterized in that: The following steps are involved: (1) mixing a cerium salt solution and a graphene oxide suspension, adding an alkali solution and mixing evenly to obtain a first mixed solution, and subjecting the mixed solution to a hydrothermal reaction to obtain a second mixed solution; (2) The second mixed solution is centrifuged, washed, freeze-dried and purified to obtain a graphene oxide-supported nano-polyhedral cerium oxide compound.

2. The method for preparing the graphene oxide-supported nano-polyhedral cerium oxide antifouling agent according to claim 1, characterized in that: In step (1), the cerium salt includes cerium nitrate; and the ratio between the cerium salt and graphene oxide is 2mmol: (7.2-28.8)mg.

3. The method for preparing the graphene oxide-supported nano-polyhedral cerium oxide antifouling agent according to claim 1, characterized in that: In the first mixed solution of step (1), the concentration of the cerium salt is 0.04-0.06 mol / L; the concentration of the alkali is 0.08-0.12 mol / L.

4. The method for preparing the graphene oxide-supported nano-polyhedral cerium oxide antifouling agent according to claim 1, characterized in that: In step (1), the alkali in the alkali solution includes sodium hydroxide.

5. The method for preparing the graphene oxide-supported nano-polyhedral cerium oxide antifouling agent according to claim 1, characterized in that: In step (1), the hydrothermal reaction is carried out at 75 to 85° C. for 22 to 26 hours.

6. The method for preparing the graphene oxide-supported nano-polyhedral cerium oxide antifouling agent according to claim 1, characterized in that: In step (1), after the cerium salt solution and the graphene oxide suspension are evenly mixed, an alkali solution is added and stirred for 25 to 35 minutes to obtain a first mixed solution.

7. The method for preparing the graphene oxide-supported nano-polyhedral cerium oxide antifouling agent according to claim 1, characterized in that: In step (2), the centrifugal conditions are: centrifugation at a speed of 8000 to 12000 rpm for 5 to 15 minutes, and then resuspending in deionized water until the supernatant is neutral.

8. The method for preparing the graphene oxide-supported nano-polyhedral cerium oxide antifouling agent according to claim 1, characterized in that: In step (2), the freeze-drying conditions are: after freezing at -60 to -80°C for 10 to 14 hours, place in a vacuum chamber for drying.

9. The graphene oxide-supported nano-polyhedral cerium oxide antifouling agent prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the graphene oxide-supported nano-polyhedral cerium oxide antifouling agent according to claim 9 in the preparation of marine antifouling coatings.

Citation Information

Patent Citations

  • Cerium oxide-graphene oxide composite material and preparation method thereof

    CN117757433A